Evaluation of Affordability and Impoverishment Effect of Cardiovascular Medicines in Iran: Effect of cardiovascular medicines in Ira - Vasheghani Farahani, Ali; Rasekh, Hamid Reza; Najafi, Sheyda; Akbari, Maryam; Rahimi, Farimah; Salehnia, Faegheh; Hemati, Homa; Jalali, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2018)
Cardiovascular disease is one of the most important causes of death in the world. There are variety of plans and strategies to treatment and prevention of CVD. Medicines have significant role in reaching the goals. Ensuring affordability of medicines is very crucial to success in these programs. The impoverishment method which focuses on the impoverishing effect of the purchasing of medicines is one of the most popular methods to quantifying affordability of medicines. We applied this method to measure affordability of cardiovascular medicines in Iran. We used two poverty lines 1.25 USD and 2 USD per day which are recommended by World Bank to access the affordability of medicines. Mono therapy with one anti platelet, Beta blocker, ACE inhibitor and Statin as well as combination therapy have been determined. Our study highlighted that the poorest households in Iran would be at risk of pushing under poverty line because of price of the medicines.